Mental Disorders Among Health Care Workers at the Early Phase of COVID-19 Pandemic in Kenya; Findings of an Online Descriptive Survey - Kwobah, Edith Kamaru; Mwangi, Ann; Patel, Kirtika; Mwogi, Thomas; Kiptoo, Robert; Atwoli, Lukoye (Frontiers in Psychiatry, 2021)
Background: Healthcare workers responding to the Corona Virus Pandemic (COVID-19) are at risk of mental illness. Data is scanty on the burden of mental disorders among Kenyan healthcare workers responding to the pandemic that can inform mental health and psychosocial support. The purpose of this study was to establish the frequency and associated factors of worry, generalized anxiety disorder, depression, posttraumatic stress disorder and poor quality of sleep among Kenyan health care workers at the beginning of COVID-19 pandemic. Methods: We conducted an online survey among 1,259 health care workers in Kenya. A researcher developed social demographic questionnaire and several standardized tools were used for data collection. Standardized tools were programmed into Redcap, (Research Electronic Data Capture) and data analysis was performed using R Core Team. In all analysis a p-value < 0.05 was considered significant. Results: 66% of the participants reported experiencing worry related to COVID-19. 32.1% had depression, 36% had generalized anxiety, 24.2% had insomnia and 64.7% scored positively for probable Post Traumatic Stress Disorder (PTSD). Depression was higher among females compared to men (36.5 vs. 26.9%, p = 0.003), workers <35 years old compared to older ones (38.1 vs. 26.4%, p < 0.001), and those who were not married compared to those who were married (40.6 vs. 27.6%, p < 0.001). Generalized anxiety was commoner among workers aged <35 years (43.5 vs. 29.3%, p < 0.001), females (41.7 vs. 29.2%, p < 0.001), those who mere not married compared to the married (45.2 vs. 31.2%, p < 0.001) and those with <10 years working experience (41.6 to 20.5%, p < 0.001). Younger health care professional had a higher proportion of insomnia compared to the older ones (30.3 vs. 18.6%, p < 0.001). Insomnia was higher among those with <10 years' experience compared to those with more than 20 years' experience(27.3 vs. 17.6%, p = 0.043) Conclusion: Many Kenyan healthcare workers in the early phase of COVID-19 pandemic suffered from various common mental disorders with young, female professionals who are not married bearing the bigger burden. This data is useful in informing interventions to promote mental and psychosocial wellbeing among Kenyan healthcare workers responding to the pandemic.